2021
DOI: 10.3390/ma14216572
|View full text |Cite
|
Sign up to set email alerts
|

A Fuzzy Logic Model for the Analysis of Ultrasonic Vibration Assisted Turning and Conventional Turning of Ti-Based Alloy

Abstract: Titanium and its alloys are largely used in various applications due its prominent mechanical properties. However, the machining of titanium alloys is associated with assured challenges, including high-strength, low thermal conductivity, and long chips produced in conventional machining processes, which result in its poor machinability. Advanced and new machining techniques have been used to improve the machinability of these alloys. Ultrasonic vibration assisted turning (UVAT) is one of these progressive mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The experiments in this study were conducted using the robust fuzzy logic DOE technique [47]. After conducting a thorough literature review [9,10,48] and preliminary experimentation, three control variables were chosen at three levels, namely the cutting environment, the cutting speed (CS), and the feed (F), as presented in Table 3. Given the bio-compatibility of AZ31, the study focused on two machining responses, surface roughness (SR) and microhardness (HV), while taking into account carbon footprints as prime response parameter.…”
Section: Methodsmentioning
confidence: 99%
“…The experiments in this study were conducted using the robust fuzzy logic DOE technique [47]. After conducting a thorough literature review [9,10,48] and preliminary experimentation, three control variables were chosen at three levels, namely the cutting environment, the cutting speed (CS), and the feed (F), as presented in Table 3. Given the bio-compatibility of AZ31, the study focused on two machining responses, surface roughness (SR) and microhardness (HV), while taking into account carbon footprints as prime response parameter.…”
Section: Methodsmentioning
confidence: 99%
“…Chen Y. ground sapphire and found that ultrasonic-assisted grinding improved the surface finish of the sapphire in the axial and tangential direction compared with ordinary grinding [ 17 ]. Muhammad Riaz applied ultrasonic vibration to a turning tool to study the influence of processing parameters on the surface roughness of titanium alloy and confirmed that the ultrasonic-assisted process could significantly reduce the cutting force and improve the sawing surface quality [ 18 ]. Sui H. et al combined ultrasonic vibration-assisted machining and boring and found that the combined approach was effective in reducing the boring force and improving the accuracy of the boring.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to turning, milling, and drilling, cutting zone research continues for a variety of other materials [38,39] and cutting technologies such as grinding [40], milling with a disc cutter [41], and Micro and Macro Machining (MMM) [42,43] by using FEM [44] and fuzzy algorithms [45].…”
Section: Introductionmentioning
confidence: 99%